Low Learning Achievements of the Learners in English Language in Elementary Schools of Tribal Areas - Pradhan, Manoranjan (JOURNAL OF INDIAN EDUCATION, 2018)
According to several reports, low learning achievements of learners in English language at the elementary schooling is a major concern and challenge. Despite the interventions and constructive strategies are being taken to promote quality education to all children between 6–14 years of age it is seen that at the end of elementary schooling, students cannot read the textbooks of their junior classes. Some of then even fail to distinguish between capital and small letters. Making spelling and grammatical errors, inability to write correct sentences or a short paragraph on their own, are several challenges in the way of improving students’ learning performance. This study is an attempt to learn from the Block Resource Group members, who are master trainers in the block about the factors responsible for the low learning achievements of the learners in English language at the elementary level of schooling. For that, 49 BRG members from Blocks (out of 14 in Koraput—a tribal dominated socio-economic and educationally backward district of Odisha) were taken as sample of the study. Besides, efforts were also made to know the major problems that teachers are facing during teaching English in class, and remedies to alleviate the problem in order to improve the learning achievements of the learners at the elementary level.